Celebrex Adjuvant Therapy on Coronavirus Disease 2019: An Experimental Study - Hong, Wenxin; Chen, Yan; You, Kai; Tan, Shenglin; Wu, Feima; Tao, Jiawang; Chen, Xudan; Zhang, Jiaye; Xiong, Yue; Yuan, Fang; Yang, Zhen; Chen, Tingting; et al. (Frontiers in Pharmacology, 2020)
Background: The pandemic of coronavirus disease 2019 (COVID-19) resulted in grave morbidity and mortality world-wide. There is currently no effective drug to cure COVID-19. Based on analyses of available data, we deduced that excessive prostaglandins E2 (PGE2) produced by cyclooxygenase-2 was a key pathological event of COVID-19. Methods: A prospective clinical study was conducted in one hospital for COVID-19 treatment with Celebrex to suppress the excessive PGE2 production. A total of 44 COVID-19 cases were enrolled, 37 cases in the experimental group received Celebrex as adjuvant (full dose: 0.2 g, bid; half dose: 0.2 g, qd) for 7-14 days, the dosage and duration was adjusted for individuals; while 7 cases in the control group received the standard therapy. The clinical outcomes were evaluated by measuring the urine PGE2 levels, lab tests, CT scans, vital signs and other clinical data. The urine PGE2 levels were measured by mass spectrometry. The study was registered and can be accessed at http://www.chictr.org.cn/showproj.aspx?proj=50474. Results: The concentrations of PGE2 in urine samples of COVID-19 patients were significantly higher than that of healthy individuals (mean value: 170 ng/ml vs 18.8 ng/ml, p<0.01) and positively correlated with the progression of COVID-19. Among those 37 experimental cases, there were 10 cases with age over 60 (27%, 10/37), 13 cases (35%, 13/37) with pre-existing conditions including cancer, atherosclerosis and diabetes etc. There were 25 cases had full dose, 11 cases with half dose of Celebrex and 1 case with Ibuprofen. The remission rates in mid-term were 100%, 82% and 57% of the full dose, half dose and control group respectively, and the discharged rate was 100% at the endpoint with Celebrex treatment. Celebrex significantly reduced the PGE2 levels and promoted recovery of ordinary and severe COVID-19. Furthermore, more complications, severity and death rate were widely observed and reported in the COVID-19 group of elders and with co-morbidities; however, this phenomenon did not appear in this particular Celebrex adjunctive treatment study. Conclusion: This clinical study indicates that Celebrex adjuvant treatment promotes the recovery of all types of COVID-19 and further reduces the mortality rate of elderly and those with co-morbidities.